PATTERN OF CUTANEOUS LEISHMANIASIS CASES AMONG TROOPS AND THEIR FAMILIES IN SIBI: Cutaneous Leishmaniasis - Ahmad, Imran; Humayun, Zill e; Ahmad, Muhammad (Pakistan Armed Forces Medical Journal, 2008)
.